Corporate social responsibility of agricultural enterprises and cooperatives: Empirical research by the fieldtrip survey in Binh Duong provinces - Vu Thanh Ha; Nguyen Chien Thang; Nguyen Viet Long (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Cooperate Social Responsibility (CSR) received a large of attention in recent years. It is one of the most important criteria in assessing the level of contribution of businesses to the community with the societies of every country in the world. According to statistics at the end of 2023, the proportion of agriculture accounts for 2.64% of the overall economic structure of Binh Duong province. However, Binh Duong always determines that agriculture and rural areas play an important role in the sustainable development of the province. Following the sustainable development and international commitments from the new generation FTAs ​​of the province’s agricultural sector, implementing corporate social responsibility is extremely necessary and strategic. Based on a survey of agricultural enterprises and cooperatives in Binh Duong province in 2023, this article introduces an overview of some positive results as well as difficulties in implementing social responsibility at agricultural enterprises/cooperatives, thereby suggesting some solutions to further strengthen the implementation of corporate social responsibility in the future. Code: 24102102